Response of the AMOC to reduced solar radiation – the modulating role of atmospheric chemistry - S. Muthers; C. C. Raible; E. Rozanov; T. F. Stocker (Earth System Dynamics, 2016)
The influence of reduced solar forcing (grand solar minimum or geoengineering scenarios like solar radiation management) on the Atlantic Meridional Overturning Circulation (AMOC) is assessed in an ensemble of atmosphere–ocean–chemistry–climate model simulations. Ensemble sensitivity simulations are performed with and without interactive chemistry. In both experiments the AMOC is intensified in the course of the solar radiation reduction, which is attributed to the thermal effect of the solar forcing: reduced sea surface temperatures and enhanced sea ice formation increase the density of the upper ocean in the North Atlantic and intensify the deepwater formation. Furthermore, a second, dynamical effect on the AMOC is identified driven by the stratospheric cooling in response to the reduced solar forcing. The cooling is strongest in the tropics and leads to a weakening of the northern polar vortex. By stratosphere–troposphere interactions, the stratospheric circulation anomalies induce a negative phase of the Arctic Oscillation in the troposphere which is found to weaken the AMOC through wind stress and heat flux anomalies in the North Atlantic. The dynamic mechanism is present in both ensemble experiments. In the experiment with interactive chemistry, however, it is strongly amplified by stratospheric ozone changes. In the coupled system, both effects counteract and weaken the response of the AMOC to the solar forcing reduction. Neglecting chemistry–climate interactions in model simulations may therefore lead to an overestimation of the AMOC response to solar forcing.